English English - Makhrozi Y, Arief; Karja, I Wayan; Suryadinata T.Y., Anak Agung Gde Trisna (Program Studi Seni Murni ISI Bali, 2025)
Art is basically created through experience, whether personal experience, other people's, socio-cultural environment, politics or religion. Art becomes a medium for artists to express ideas, concepts, from experiences felt, which are manifested in a beautiful and meaningful work of art. Along with the development of the times, art also develops. This means that the development of art is something that cannot be avoided. Likewise in the Jagratara installation artwork, with the use of technology, this Jagratara installation artwork is present as a new color in the world of art. This installation artwork is inseparable from the results of several methods carried out by the creator, including the recycle method and the exploration method. The Recycle method is a process of turning used materials into new materials with the aim of preventing waste that can actually be something of artistic value, while the media exploration method is a method as a medium to express the potential and creativity of the compiler. Basically, this method is used as an ability to find, create, redesign, and combine new or old things or ideas into new combinations of various mediums, techniques, ideas and personal interpretations in depicting the reality chosen to be visualized. Jagratara comes from Sanskrit which means always alert. The word always be alert is often heard when signs of danger begin to appear. Always be alert is a reminder sentence that is often said when danger is coming. This installation artwork is present with the aim of being a reminder and reflection on the negative impacts of plastic use, especially for marine ecosystems.